Pembentukan Karakter Anak Sebagai Wujud Imitasi Perilaku Orang Tua - cherish, lidya (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Parents are the main and most important agents in providing examples of good behavior to children, in order to build children's character so that they can become good individuals. Children will see everything that happens around them, especially what their parents do. Therefore, parents should be a good role model in order to be able to form good children's character as well. However, environmental influences can also have such a big impact on the process of forming a child's character. So the purpose of this study is to analyze the formation of children's character, whether most are formed from imitation of parental behavior or are there other factors that are more dominant in shaping children's character. This research uses qualitative methods by collecting data through observation, interviews, and documentation. Then the data that has been collected will be analyzed using the perspective of symbolic interactionism theory by George Herbert Mead. The research results obtained are that the formation of children's character is greater as a form of imitation of parental behavior which since in the womb, children have been able to respond to actions taken by parents, especially mothers, but do not rule out the possibility that there are other factors that influence the formation of children's character.